2022
DOI: 10.5498/wjp.v12.i9.1150
|View full text |Cite
|
Sign up to set email alerts
|

Depressive disorder and antidepressants from an epigenetic point of view

Abstract: Depressive disorder is a complex, heterogeneous disease that affects approximately 280 million people worldwide. Environmental, genetic, and neurobiological factors contribute to the depressive state. Since the nervous system is susceptible to shifts in activity of epigenetic modifiers, these allow for significant plasticity and response to rapid changes in the environment. Among the most studied epigenetic modifications in depressive disorder is DNA methylation, with findings centered on the brain-derived neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 102 publications
0
3
0
Order By: Relevance
“…These small molecules accomplish essential post-transcriptional regulatory steps of gene expression through either the degradation of an mRNA transcript or the inhibition of translation ( He and Hannon, 2004 ). Both in the peripheral and central nervous systems, miRNAs are considered potential biomarkers in the diagnosis of MDD and in monitoring therapeutic responses ( Šalamon Arèan et al, 2022 ). They regulate key processes in the central nervous system including neuronal development, neurogenesis, and synaptic plasticity, while in the periphery they are implicated with immune and endocrine regulation, for instance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These small molecules accomplish essential post-transcriptional regulatory steps of gene expression through either the degradation of an mRNA transcript or the inhibition of translation ( He and Hannon, 2004 ). Both in the peripheral and central nervous systems, miRNAs are considered potential biomarkers in the diagnosis of MDD and in monitoring therapeutic responses ( Šalamon Arèan et al, 2022 ). They regulate key processes in the central nervous system including neuronal development, neurogenesis, and synaptic plasticity, while in the periphery they are implicated with immune and endocrine regulation, for instance.…”
Section: Resultsmentioning
confidence: 99%
“…The methylation of nucleobases can change the functionality of a segment of DNA without altering the sequence. Studies have shown altered DNA methylation patterns associated with MDD and antidepressants ( Webb et al, 2020 ; Šalamon Arèan et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…As EVs can cross the BBB and later circulate in the CSF, their contents can serve as biomarkers of the pathological processes that might be happening in the brain. One of the most promising biomarkers of different neurological disorders is miRNAs, which have been identified as the cargo of EVs (Mori et al, 2019;Šalamon Arčan et al, 2023).…”
Section: Csf Compositionmentioning
confidence: 99%
“…Studies often focus on brain regions related to emotional and behavioral responses, and cognitive and executive control functions. These often-studied regions include the limbic system (hippocampus) and the prefrontal cortex (PFC) (Brodmann area 9 in the dorsolateral PFC)[ 33 , 34 ]. Since the brain is not accessible during life, other peripheral, more easily accessible tissues, such as blood, are often included in studies of psychiatric disorders as well.…”
Section: Current Overview Of Dna Hydroxymethylation Studies and Psych...mentioning
confidence: 99%